PENGARUH PERSEPSI STATUS SOSIAL GURU PADA MAHASISWA PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU TERHADAP MINAT MENJADI GURU - Elsa Maya; Nana Rahayu; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study is to determine and explain how much influence between the perception of the social status of teachers on students' interest in becoming teachers. This research is descriptive research with a quantitative approach. The sample of this research was students of the Class of 2019 and 2020 of the Japanese Language Education Study Program, Language and Arts Education, Teachers Training and Education Faculty, Riau University, totaling 60 people and the data obtained were 52 students. Data analysis techniques are described using descriptive statisticalsimple linear regression analysis to answer problem formulations and hypotheses. Furthermore, the data will be analyzed using correlation using the help of the IBM SPSS 22.0 program. The results of the study showed a positive and significant effect of perceived social status of teachers on interest in becoming a teacher.Key Words: Influence; Teacher Social Status; Interest In Becoming A Teacher